2014
DOI: 10.25311/keskom.vol2.iss5.73
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penyakit Penyerta Kehamilan dan Kehamilan Ganda dengan Kejadian Bayi Berat Lahir Rendah di RSUD Arifin Achmad Provinsi Riau

Abstract: Data yang diperoleh dari Rekam Medik RSUD Arifin Achmad Provinsi Riau dari tahun 2011 sampai 2013 untuk kejadian BBLR yaitu pada tahun 2011 tercatat 46 kasus (1,62%) dari 2833 persalinan, tahun 2012 tercatat 179 kasus (5,44%) dari 3290 persalinan dan tahun 2013 tercatat 130 kasus (4,56%) dari 2848 persalinan dan BBLR masih termasuk ke dalam 3 besar dari 15 penyakit penyebab kematian Neonatal. Tujuan  penelitian  adalah diketahuinya faktor-faktor yang berhubungan dengan kejadian BBLR di RSUD Arifin Achmad Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Furthermore, there was a significant relationship between multiple pregnancies and the incidence of LBW (p= 0.000). It is in line with previous research by Triana (2016), revealing that mothers with multiple pregnancies were 15 times more at risk of giving birth to babies with LBW (95% CI 4.8-45.1). In addition, studies also showed that multiple pregnancies were associated with LBW incidence (Merzalia, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there was a significant relationship between multiple pregnancies and the incidence of LBW (p= 0.000). It is in line with previous research by Triana (2016), revealing that mothers with multiple pregnancies were 15 times more at risk of giving birth to babies with LBW (95% CI 4.8-45.1). In addition, studies also showed that multiple pregnancies were associated with LBW incidence (Merzalia, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…IDHS in 2012 stated that this disorder also has the highest risk of death in comparison with normal birth weight, particularly during the perinatal period [18].…”
Section: Prevalencementioning
confidence: 99%